DECOLONIZING JAVA: RETHINKING GAMELAN, BODIES, AND CULTURAL AUTHENTICITY - Aryandari, Citra (Paradigma: Jurnal Kajian Budaya, 2025)
This article critically examines the complex interactions between Javanese identity, colonial influence, and karawitan (traditional Javanese music) through an autoethnographic methodology. By introducing the innovative concept of the ‘body as archive,’ the research explores how embodied experiences function as repositories of cultural memory and resistance. It deconstructs colonial interventions in karawitan, uncovering how documentation, standardization, and systematic recording processes altered the transmission and cultural significance of the art form. The research traces the transition from oral traditions to written documentation, highlighting the commodification of Javanese artistic expressions and the emergence of cultural stereotypes. A central focus of this study is the exploration of embodied knowledge as a decolonial strategy. By emphasizing local wisdom and personal narratives, the article demonstrates how performative practices such as karawitan can serve as potent sites for cultural reclamation and identity negotiation. The analysis ultimately challenges conventional perspectives on cultural preservation, contending that evolving artistic traditions have the potential to reshape and reimagine Javanese identity in a postcolonial context.